Understanding The Drivers and Barriers Towards Sustainable Consumption: An Approach by Linking a Pedagogical Strategy of Active Learning with Adopting Sustainable Behaviors by Students - Arias, Claudia (Journal of Sustainability Perspectives, 2024)
Adopting sustainable consumption behaviors is imperative for achieving better sustainable production and consumption patterns (SDG12). Individuals play a crucial role in this goal as both part of the problem and the solution. Consequently, various actors aim to address the factors influencing individuals' adoption of these behaviors. Among these actors, higher education institutions play a unique role due to their opportunity to guide future generations through Education for Sustainable Consumption (ESC) towards sustainable values, attitudes, competencies, and behaviors. Understanding the drivers and barriers individuals face toward sustainable consumption is crucial for actively pursuing sustainability. However, few efforts have addressed this problem based on the actual experiences of individuals, and even fewer have focused on students as individuals who will hopefully lead organizations with a sustainability mindset. This research aims to fill this gap by linking a pedagogical strategy of active learning to the adoption of sustainable behaviors. Using a qualitative approach, we analyzed the experiences that students reported over three academic semesters in an online forum. The findings reveal that barriers to adopting sustainable behaviors are mostly contextual, while internal factors motivate people to advance toward this type of practice. From this methodological approach, emergent factors provide insights that could guide future policies and strategies to achieve better sustainable consumption patterns.